Compatibility of Trichoderma isolates with pesticides used in lettuce crop - Silva,Micaele Aparecida Franco da (2018)
ABSTRACT Lettuce drop, caused by Sclerotinia minor and S. sclerotiorum, is one of the most important diseases that affect lettuce crop in Brazil. In previous studies, isolates of Trichoderma asperellum (IBLF 897, IBLF 904 and IBLF 914) and T. asperelloides (IBLF 908) were selected for the biocontrol of this disease. In this subsequent study, the compatibility of these isolates with pesticides used in lettuce crop in Brazil was evaluated. Initially, the mycelial growth of isolates was evaluated in culture medium plus pesticides. Then, the effect of pesticides on the parasitism of T. asperelloides isolate IBLF 914 in baits and sclerotia of S. minor and S. sclerotiorum, as well as on the survival of lettuce seedlings, was evaluated in gerboxes after application on baits and sclerotia of the antagonist with pesticides at their respective commercial doses. The fungicides pencycuron and mandipropamid and the insecticide imidacloprid did not affect the mycelial growth of Trichoderma isolates. The fungicide iprodione did not affect the mycelial growth of T. asperellum isolates. but the isolate of T. asperelloides was sensitive from the concentration of 10 µg.L-1 fungicide. Procymidone reduced the mycelial growth of Trichoderma isolates from the concentration of 10 µg.L-1 fungicide, and azoxystrobin reduced the conidial germination of the isolates of the antagonist, showing LD50 between 0.36 and 0.42 µg.L-1 fungicide. On the other hand, in the experiment carried out in “gerboxes”, none of the pesticides reduced the parasitism of baits and sclerotia or reduced the control of S. minor and S. sclerotiorum in lettuce seedlings. Results indicate that the biological control of lettuce drop with T. asperelum isolate IBLF 914 can be compatible with the remaining phytosanitary treatments used in lettuce crop.